A review of foodborne bacterial and parasitic zoonoses in Vietnam. - Carrique-Mas, J; Bryant, J (2013)
Vietnam has experienced unprecedented economic and social development in recent years, and the livestock sector is undergoing significant transformations. Although food animal production is still dominated by small-scale 'backyard' enterprises with mixed crop-livestock or livestock-aquatic systems, there is a trend towards more intensive and vertically integrated operations. Changes in animal production, processing and distribution networks for meat and animal products, and the shift from wet markets to supermarkets will undoubtedly impact food safety risks in Vietnam in unforeseen and complex ways. Here, we review the available published literature on bacterial and parasitic foodborne zoonoses (FBZ) in Vietnam. We report on clinical disease burden and pathogen prevalence in animal reservoirs for a number of important FBZ, and outline opportunities for future research.